Consensus of second-order multi-agent systems with random sampling via event-triggered control. Issue 6 (April 2016) - Mu, Nankun; Liao, Xiaofeng; Huang, Tingwen
Abstract: In this paper, the consensus problem of second-order multi-agent systems is considered, where the data is sampled randomly and the topology has a directed spanning tree. An event-triggered control protocol based on the random sampling data and an improved time-dependent threshold is proposed for the consensus of second-order multi-agent systems, and thus the data transmission can be effectively reduced. Under some reasonable assumptions, the sufficient conditions are derived for assuring the second-order consensus based on the proposed event-triggered control protocol. Finally, some numerical examples are provided to demonstrate the effectiveness of the proposed event-triggered control protocol.